2020
DOI: 10.1002/cctc.201902081
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Nanomaterial‐based Water Treatment Approaches for Photocatalytic Degradation of Water Pollutants

Abstract: Demand of pure drinking water is increasing day by day in line with both a growing population and global industrialization. Studies in the past few decades on the application of advanced oxidation processes (AOP) for the treatment of wastewater containing perilous organic pollutants, are promising when compared to conventional water treatment methods. In case of AOP, generation of powerful oxidant radicals (.OH, HOO.) is crucial for the purpose of degradation. Several processes for the in‐situ generation of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 140 publications
3
35
0
Order By: Relevance
“…A number of studies had shown that the photocatalytic rate would decrease when the catalyst dosage exceeded a certain amount , because at higher catalyst dosages, light scattering, catalyst particle agglomeration, and turbidity of the solution would increase, which led to a decrease in the light passing through the suspension and the surface area of the catalyst that absorbed light . The optimal dosage depended on the geometry, the working conditions of the photoreactor, and the type of UV lamp (power, wavelength, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies had shown that the photocatalytic rate would decrease when the catalyst dosage exceeded a certain amount , because at higher catalyst dosages, light scattering, catalyst particle agglomeration, and turbidity of the solution would increase, which led to a decrease in the light passing through the suspension and the surface area of the catalyst that absorbed light . The optimal dosage depended on the geometry, the working conditions of the photoreactor, and the type of UV lamp (power, wavelength, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…The photoactivity of titania has been widely applied for environmental remediation; for instance, through the generation of graphene-bearing membranes for water purification [186,206]. The mechanisms of titania-photocatalyzed dye degradation proceed through the generation of reactive oxygen species (ROS) that trigger the photooxidation of organic molecules [207]. This phenomenon can be applied to a variety of different pollutants.…”
Section: Photocatalysis For Environmental Remediationmentioning
confidence: 99%
“…Examples of such organic pollutants include pesticides originating from agricultural activities, pharmaceuticals and personal care products emanating from pharmaceutical industries, hospitals and households, and organic dyes originating from textile industries. 4 The textile sector remains a robust sector responsible for more than 800 tons of synthetic dyes yearly. 5 Unfortunately, more than 10% of this dyestuff ends up in the environment as constituents of untreated or improperly treated effluents.…”
Section: Introductionmentioning
confidence: 99%